Priority Management of Henle Trunk in Cranial-to-Caudal Approach for Laparoscopic Right Hemicolon Cancer Surgery - Yang, Yao; Jiang, Xiaohua; Zhou, Zhuqing; Lu, Bing; Zhu, Zhe; Jiang, Qixing; Ji, Fang; Fu, Chuangang (Frontiers in Surgery, 2022)
This study aimed to compare the short-term clinical efficacy between prior and traditional approach of Henle trunk in laparoscopic right hemicolectomy (LRH) for right colon cancer. A total of 161 patients underwent LRH for right colon cancer between June 2018 and December 2020 by the same group of physicians. The prior approach of Henle trunk (priority group) was used in 82 patients and traditional approach in 79 (traditional group). The demographics and clinopathological characteristics were recorded and retrospectively analyzed. As compared to the traditional group, the mean blood loss reduced significantly [73.84±17.31 mL vs 83.42±30.16 mL; P=0.001], the operation time was markedly shorter [151.35±6.75 min vs 159.13±18.85 min; P=0.014], and the intraoperative vascular injury rate was significantly lower [6.1% (5/82). vs. 17.7% (14/79); P=0.022]. There were no significant differences in the postoperative complications, first exhaust time, first defecation time, drainage time, postoperative hospital stay, quality evaluation of surgical specimens and pathological findings between two groups. Our study shows that the priority management of Henle trunk in the LRH for right colon cancer is a safe and feasible procedure with less blood loss, shorter operation time and lower intraoperative vascular injury rate.